2009
DOI: 10.1590/s0100-69162009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de alface hidropônica em três ambientes de cultivo

Abstract: Propôs-se avaliar a produção hidropônica de alface-crespa, variedade "Vera", em bancadas inclinadas com canais de 100 mm, utilizando a técnica de filme de solução nutritiva, em resposta à aplicação de dióxido de carbono e ao resfriamento evaporativo. Realizaram-se cinco ciclos de cultivo nos períodos de 20-3 a 17-4-2000 (C1); 25-5 a 29-6-2000 (C2); 13-7 a 21-8-2000 (C3); 27-8 a 2-10-2000 (C4) e 12-12-2000 a 10-1-2001 (C5). Avaliaram-se três casas de vegetação, sendo casa de vegetação sem sistema de resfriament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Hydroponics have several advantages including the possibility of using areas unsuitable for conventional farming, such as arid and degraded soils, independence of the crop to weather conditions leading to its cultivation all over the year [17], and reduction in the use of labor-intensive activities such as weeding and soil preparation. This technique allowed a reduction in the plant cycle (45 -60 days), leading to an anticipated harvest; moreover, it enabled an active crop rotation, improved financial returns, and an efficient use of cultivation resources specially water and nutrients, while maintaining great environmental benefit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroponics have several advantages including the possibility of using areas unsuitable for conventional farming, such as arid and degraded soils, independence of the crop to weather conditions leading to its cultivation all over the year [17], and reduction in the use of labor-intensive activities such as weeding and soil preparation. This technique allowed a reduction in the plant cycle (45 -60 days), leading to an anticipated harvest; moreover, it enabled an active crop rotation, improved financial returns, and an efficient use of cultivation resources specially water and nutrients, while maintaining great environmental benefit.…”
mentioning
confidence: 99%
“…Hydroponic systems weren't only associated to an increase in production yields, but also to a reduction in the overall production costs by enabling better control and standardization of the production process [13] [17]. In hydroponic crops, absorption is usually proportional to the concentration of nutrients in the solution near the roots influenced by the salinity, oxygenation, temperature and pH of the nutrient solution [13].…”
mentioning
confidence: 99%
“…The objective of this study was to perform a literature review of authors who have researched comparisons between different environmental conditions and their correlation with plant performance. Costa & Leal (2009) observed that in hydroponic production of lettuce, variety Vera, in three greenhouses, one without evaporative cooling and CO 2 injection, another with injection of CO 2 and without evaporative cooling and a third, with CO 2 injection and evaporative cooling (acclimatized), the environment with evaporative cooling and CO 2 injection promoted the best development of plants with larger leaves. In acclimatized environment with evaporative cooling, Costa & Leal (2008) found greater accumulation of leaf biomass and greater leaf area of strawberry plants than in nonacclimatized environments, regardless of the season (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A Tabela 8 mostra que o valor médio diário de RFA que atingiu o dossel das plantas ficou abaixo do ponto de saturação luminosa no ambiente com tela termorrefletora (Ambiente 1), enquanto que no Ambiente 2 a média se aproximou ao limite inferior da faixa de saturação luminosa compreendida entre 700 e 1.500 µmol s -1 m -2 , de acordo com valores citados por ROCHA (2007) e PAPADOPOULOS e HAO (1997) para diferentes genótipos de tomateiro. No entanto, entre 9h e 15h, período no qual as plantas são mais ávidas pela realização da fotossíntese (COSTA e LEAL, 2009), o valor de RFA ultrapassou, no Ambiente 2, o valor de 1.500 µmol s -1 m -2 em 79 % dos dias registrados, ao passo que no Ambiente 1 os valores máximos de RFA ficaram entre 700 e 1.500 µmol s -1 m -2 em 68% dos dias e, em apenas 20 % dos dias ficaram acima de 1.500 µmol s -1 m -2 . ANDRIOLO (2000) destaca que a alta radiação, somada a ocorrência de altas temperaturas, pode degradar os pigmentos de clorofila, reduzir a fotoassimilação de hidratos de carbono e aumentar a…”
Section: Radiação Fotossinteticamente Ativaunclassified